PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS (NH) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PULAU PUNJUNG - Novita, Rici; Zuzano, Fazri; Yunita, Alfi (Pendidikan Matematika, 2013)
This research was background by student understanding of mathematical concept is still low. This matter seen at result learn class student mathematics of VII which enlist in class of VIII SMPN 1 Pulau Punjung School Year 2013 / 2014. He aim of this research model is to know the understanding of mathematical concept by applying model study with cooperative type NH accompanied by quiz better than student understanding of mathematical concept conventional study in class of VIII SMPN 1 Pulau Punjung. This type of this  research is experiment. Research with random sampling techniques. Population in this research is all class student of VIII SMPN 1 Pulau Punjung school year 2013 /2014 except class VIII1 representing preeminent class. The selected class of sampel is VIII4 as experiment class and of VIII5 as control class. Instrument used in this research is the tes of  understanding of mathematical concept. Form of tes the used is form of esai with reliabilitas test is r11=0,92. Technique analyse data  used in this test is t. According to result of data analysis known that both class of sampel have normal distribution and is not homogeneous at real level = 0,05. Result of hypothesis test obtained by t=3,73 bigger than ttable=1,23 hence hypothesis at this research is accepted. So that can be concluded that student  understanding of mathematical concept by applying model study with cooperative learning type NH accompanied by quiz better than student understanding of mathematical concept with conventional study in class of VIII SMPN 1 Pulau Punjung.